ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN KONSUMEN DALAM PEMEMBELIAN PERUMAHAN DI SURAKARTA - TUTI EDIATI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2014)
The purpose of this researchÂ is: (1) To measure the extent to which consumer attitudes toward product attributes housing type 45/90 in the city of Surakarta which include price, location, quality of construction, and the environment. (2) To test and measure the partial effect between price, location, quality of construction, and the environment of the home purchase decision type 45/90 in the city of Surakarta. (3) To test and measure the simultaneous effect between price, location, quality of construction, and the environment of the home purchase decision type 45/90 in the city of Surakarta. The researchÂ was conducted in a residential-type 45/90 housing Surakarta city built by the developers. The population in this research is the number of consumers who have bought a house type 45/90 in the city of Surakarta. Samples were taken of 100 respondents with a cluster sampling technique. The analysis technique used is using index analysis, multiple linear regression, t test, the F test and coefficient of determination. The results of the research found that found that positive consumer attitudes toward product attributes housing type 45/90 in the city of Surakarta. This means that the people in Surakarta accept both the existence of housing type 45/90. Partially and simultaneously there is influence between price, location, building and the environment against the decision of consumers in the purchase of housing types 45/90 in Surakarta city. Decisions of consumers in the purchase of housing types 45/90 in the city of Surakarta influenced by factors of price, location, building and the environment by 91.70% and the remaining 8.30% is influenced by other variables that are not observed in this research. Â